The Effect of Seeds Number and Modified Jajar Legowo Planting System to The Growth and Yield for Rice (Oryza sativa L.) in Medan Tuntungan - Stephanie Claudia Chrisdyana Tambunan; Posma Marbun; Erwin Masrul Harahap (Universitas Sumatera Utara, 2018)
The research was conducted at rice field in Medan Tuntungan which about ± 25 metres above sea level, begun from March until June 2017 using completly randomized design with two factors, i.e: the number of seeds (1,2,3) and plant population based on modified jajar legowo planting system (conventional planting system with population of 48 clumps per plot, jajar legowo planting system with population of 60 clumps per plot, jajar legowo planting system with population of 114 clumps per plot, jajar legowo planting system with population of 154 clumps per plot, jajar legowo planting system with population of 190 clumps per plot). The results showed that 1 seed of clumps with conventional planting system with population of 48 clumps per plot significantly influence the increase of rice production (Oryza sativa L.). The interaction between number of seeds dan plant population significantly increased growth but did not significantly increase rice production (Oryza sativa L.). Keywords : jajar legowo, number of seeds, rice